Bone Marrow Transplant for Low Risk Thalassemia Patients in Low Resource Setting - Yaqub, Naila; Fatima, Itrat; Khalid, Sadaf (International Journal of Pathology, 2018)
Objective: To evaluate performance of a newly developed low resource Bone Marrow Transplant unitfor thalassemia major in Islamabad.Materials and Methods: Medical Records of 26 bone marrow transplants performed were revisited.Their survivals, complications, management of complications and cost of treatment were evaluated.Results: 23 had successful engraftment with transfusion free survival. Two patients had transplant relatedmortality. The manageable complications included hypertension and hemorrhagic cystitis. Onepatient developed VOD.Conclusion: Bone Marrow transplant for transfusion dependent Thalassemia is possible in low resourcesetup with results that are comparable with the centers in developed countries and the complicationsare manageable.